The role of the BK channel in ethanol response behaviors: evidence from model organism and human studies - Bettinger, Jill C.; Davies, Andrew G. (Frontiers in Physiology, 2014)
Alcohol abuse is a significant public health problem. Understanding the molecular effects of ethanol is important for the identification of at risk individuals, as well as the development of novel pharmacotherapies. The large conductance calcium sensitive potassium (BK) channel has emerged as an important player in the behavioral response to ethanol in genetic studies in several model organisms and in humans. The BK channel, slo-1, was identified in a forward genetics screen as a major ethanol target in C. elegans for the effects of ethanol on locomotion and egg-laying behaviors. Regulation of the expression of the BK channel, slo, in Drosophila underlies the development of rapid tolerance to ethanol and benzyl alcohol sedation. Rodent expression studies of the BK-encoding KCNMA1 gene have identified regulation of mRNA levels in response to ethanol exposure, and knock out studies in mice have demonstrated that the beta subunits of the BK channel, KCNMB1 and KCNMB4, can modulate ethanol sensitivity of the channel in electrophysiological preparations, and can influence drinking behavior. In human genetics studies, both KCNMA1 and the genes encoding beta subunits of the BK channel have been associated with alcohol dependence. This review describes the genetic data for a role for BK channels in mediating behavioral responses to ethanol across these species.